The Use of Interactions Between Microorganisms in Strawberry Cultivation (Fragaria x ananassa Duch.) - Drobek, Magdalena; Cybulska, Justyna; Gałązka, Anna; Feledyn-Szewczyk, Beata; Marzec-Grządziel, Anna; Sas-Paszt, Lidia; Gryta, Agata; Trzciński, Paweł; Zdunek, Artur; Frąc, Magdalena (Frontiers in Plant Science, 2021)
As the market indicates a growing interest in organically grown fruit, there is a need for biostimulants to counter the adverse effects of pathogenic fungi and fungal-like-pathogens. Four microbial pathogens (Botrytis cinerea, Verticillium sp., Phytophthora sp., Colletotrichum sp.) which are the most often causes of strawberry diseases were selected. Five kinds of biostimulants (C1, C2, C3, C4, C5) containing bacterial consortia were developed to combat the pathogens. The antagonistic effect of selected microorganisms against strawberry pathogens was observed. The effectiveness of various beneficial bacteria in combating fungal pathogens of cv. Honeoye strawberries was compared and the impact of their activity on fruit quality was assessed. The most significant effect on the strawberry firmness was found for the C2 consortium, which provided the strawberries infected with the pathogens group (MIX: B. cinerea, Verticillium sp., Phytophthora sp., Colletotrichum sp.) with a 140 % increase in maximum load in a puncture test compared to the positive control (C0). %Strawberries contaminated with Phytophthora sp. after the application of Consortium C4 (C4) showed the largest increase (127 %) in soluble solid content (SSC) when compared to the C0. Fruit contaminated with Colletotrichum sp. and B. cinerea after the application of C2 and Consortium 5 (C5), respectively, had the highest levels of anthocyanins and total phenolic content, when compared to C0. The largest increase, which reached as high as 25 %, in D-galacturonic acid content was observed for the group of pathogens after Consortium 1 (C1) application. The extraction of strawberry pectin allowed for the study of the rheological properties of pectin solutions; on this basis, strawberry pectin from the control (NC) was distinguished as it showed the highest viscosity (0.137-0.415 Pas). Taking into account the individual effects of bacteria on strawberry pathogenic fungi and fungal-like-pathogens, it is possible to reduce the adverse effects of fungal disease and to improve the properties of strawberries by selecting the appropriate bacterial consortium. Interactions between microorganisms are often complex and not fully understood, which suggests the need for further research in this direction.